Is a mass drug administration deworming programme for school-aged children enough to reduce the prevalence of soil-transmitted helminths and Schistosoma mansoni in adults: a cross-sectional study from Togo - Simfele, Hombamane Christelle; Katawa, Gnatoulma; Arndts, Kathrin; Tchopba, Christèle Nguepou; Amessoudji, Oukoe Marthe; Tchadie, Edlom Pélagie; Karou, Simplice Damintoti; Ameyapoh, Yaovi; Hoerauf, Achim; Kolou, Malewe; Layland-Heni, Laura; Ritter, Manuel (Frontiers in Tropical Diseases, 2024)
Background The world health organization (WHO) introduced the mass drug administration (MDA) strategy in order to reduce the prevalence of soil-transmitted helminths (STHs) and Schistosoma mansoni in endemic areas. However, this strategy is not implemented in adult population in Togo. Thus, the question arose if the present MDA strategy contributes to the reduction of transmission rates. The present study aimed to monitor the prevalence of STHs and S. mansoni among adult’s, between 2017 and 2022, in the central region of Togo. Methods Two cross-sectional studies were conducted in six villages in the central region of Togo in 2017 and 2022. Stool samples were collected from adults over the age of 18 years. To assess STHs and S. mansoni infections, real-time multiplex qPCR and Kato-Katz techniques were performed. Data were analysed using SPSS software version 21 and GraphPad PRISM version 9.2.0. A p-value less than 0.05 was considered statistically significant. Results A total of 210 and 289 individuals were recruited in 2017 and 2022, respectively. We detected significant increase in the prevalence of STHs and S. mansoni from 7.61% to 24.56% (p=0.0008) and from 27.62% to 46.36% (p=0.0014) by Kato-Katz and RT-qPCR, respectively. The prevalence of Ancylostoma duodenale infection was the highest with an increase from 7.14% to 23.53% by Kato-Katz and 9.09% to 40.0% by RT-qPCR. Conclusion The prevalence of STHs and S. mansoni increased in the adult population in the central region of Togo from 2017 to 2022, despite the implementation of MDA in school-aged children. Hence, there is an urgent need to include adult individuals and adapt the MDA programme in the central region of Togo.